Possible Footprints of APOBEC3F and/or Other APOBEC3 Deaminases, but Not APOBEC3G, on HIV-1 from Patients with Acute/Early and Chronic Infections - Armitage, Andrew E. (J Virol, 2014)
Members of the apolipoprotein B mRNA-editing enzyme-catalytic polypeptide-like-3 (APOBEC3) innate cellular cytidine deaminase family, particularly APOBEC3F and APOBEC3G, can cause extensive and lethal G-to-A mutations in HIV-1 plus-strand DNA (termed hypermutation). It is unclear if APOBEC3-induced mutations in vivo are always lethal or can occur at sublethal levels that increase HIV-1 diversification and viral adaptation to the host. The viral accessory protein Vif counteracts APOBEC3 activity by binding to APOBEC3 and promoting proteasome degradation; however, the efficiency of this interaction varies, since a range of hypermutation frequencies are observed in HIV-1 patient DNA. Therefore, we examined “footprints” of APOBEC3G and APOBEC3F activity in longitudinal HIV-1 RNA pol sequences from approximately 3,000 chronically infected patients by determining whether G-to-A mutations occurred in motifs that were favored or disfavored by these deaminases. G-to-A mutations were more frequent in APOBEC3G-disfavored than in APOBEC3G-favored contexts. In contrast, mutations in APOBEC3F-disfavored contexts were relatively rare, whereas mutations in contexts favoring APOBEC3F (and possibly other deaminases) occurred 16% more often than average G-to-A mutations. These results were supported by analyses of >500 HIV-1 env sequences from acute/early infection. IMPORTANCE Collectively, our results suggest that APOBEC3G-induced mutagenesis is lethal to HIV-1, whereas mutagenesis caused by APOBEC3F and/or other deaminases may result in sublethal mutations that might facilitate viral diversification. Therefore, Vif-specific cytotoxic T lymphocyte (CTL) responses and drugs that manipulate the interplay between Vif and APOBEC3 may have beneficial or detrimental clinical effects depending on how they affect the binding of Vif to various members of the APOBEC3 family.